Dynamics and Balancing of Multibody Systems - Chaudhary, Himanshu; Saha, Subir Kumar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This monograph develops a unified methodology for dynamic analysis and minimization of the inertia-induced forces occurring in high speed multiloop planar as well as spatial mechanisms based on the multibody system modeling approach. Dynamic analysis is prerequisite for the dynamic balancing of mechanisms. The balancing of mechanisms is one of the crucial steps in design of high speed machinery and is a difficult one due to trade-off amongst various dynamic quantities, e.g., shaking force, shaking moment, bearing reactions, and driving torques/forces. Hence, it is essentially an optimization problem where various dynamic quantities are computed repeatedly.
Dynamics of Open-loop Systems -- Dynamics of Closed-loop Systems -- Equimomental Systems -- Balancing of Planar Mechanisms -- Balancing of Spatial Mechanisms.
Keywords: Engineering; Applied mathematics; Engineering mathematics; Mechanics; Mechanics, Applied; Vibration; Dynamical systems; Dynamics; Mechanical engineering; Materials science; Engineering; Mechanical Engineering; Materials Science, general; Theoretical and Applied Mechanics; Appl.Mathematics/Computational Methods of Engineering; Vibration, Dynamical Systems, Control; Electronic books